Back-analysing rock mass modulus from monitoring data of two tunnels in Sydney, Australia - Robert Bertuzzi (Journal of Rock Mechanics and Geotechnical Engineering, 2017)
This paper presents two case studies where the rock mass modulus and in situ stress are estimated from the monitoring data obtained during the construction of underground excavations in Sydney, Australia. The case studies comprise the widening of existing twin road tunnels within Hawkesbury sandstone and the excavation of a large cavern within Ashfield shale. While back-analysis from detailed systematic monitoring has been previously published, this paper presents a relatively simple methodology to derive rock mass modulus and in situ stress from the relatively simple displacement data routinely recorded during tunnelling.